Psychometric properties of the patient assessment of chronic illness care measure: acceptability, reliability and validity in United Kingdom patients with long-term conditions - Rick Jo; Rowe Kelly; Hann Mark; Sibbald Bonnie; Reeves David; Roland Martin; Bower Peter (BMC, 2012)
Abstract Background The Patient Assessment of Chronic Illness Care (PACIC) is a US measure of chronic illness quality of care, based on the influential Chronic Care Model (CCM). It measures a number of aspects of care, including patient activation; delivery system design and decision support; goal setting and tailoring; problem-solving and contextual counselling; follow-up and coordination. Although there is developing evidence of the utility of the scale, there is little evidence about its performance in the United Kingdom (UK). We present preliminary data on the psychometric performance of the PACIC in a large sample of UK patients with long-term conditions. Method We collected PACIC, demographic, clinical and quality of care data from patients with long-term conditions across 38 general practices, as part of a wider longitudinal study. We assess rates of missing data, present descriptive and distributional data, assess internal consistency, and test validity through confirmatory factor analysis, and through associations between PACIC scores, patient characteristics and related measures. Results There was evidence that rates of missing data were high on PACIC (9.6% - 15.9%), and higher than on other scales used in the same survey. Most PACIC sub-scales showed reasonable levels of internal consistency (alpha = 0.68 - 0.94), responses did not demonstrate high skewness levels, and floor effects were more frequent (up to 30.4% on the follow up and co-ordination subscale) than ceiling effects (generally <5%). PACIC demonstrated preliminary evidence of validity in terms of measures of long-term condition care. Confirmatory factor analysis suggested that the five factor PACIC structure proposed by the scale developers did not fit the data: reporting separate factor scores may not always be appropriate. Conclusion The importance of improving care for long-term conditions means that the development and validation of measures is a priority. The PACIC scale has demonstrated potential utility in this regard, but further assessment is required to assess low levels of completion of the scale, and to explore the performance of the scale in predicting outcomes and assessing the effects of interventions.